A test of market efficiency using stock market anomalies: a behavioural approach. (17th June 2019) - Abdin, Syed Zain Ul; Waqas, Muhammad; Ahmad, Mumtaz
Previous researchers study the presence of anomalies in the stock market but very few studies identify the causes that generate anomalies. This study tests the efficient market hypothesis in the context of prospect theory. The main aim of this study is to examine the effect of behavioural factors on different classes of anomalies. Further, the paper investigates the differential effect of prospects components on different classes of anomalies. Data collected from 324 real individual investors of Pakistani Stock Exchange. Structural equation modelling was used to test the hypothesised model using smart PLS 3.0. The results show that mental accounting has a positive significant effect on all anomalies. In short, investors use their own mental account in their decision-making. Loss aversion has a positive significant effect on technical anomalies and regret has a positive significant effect on fundamental anomalies. However, self-control does not have a significant effect on technical and calendar anomalies.